Sustainability status of People's Salt Pond Businesses in the coastal area of Labakkang District Pangkep Regency - Rauf, Abdul; Yusuf, Kamil; Yunus, Muhammad; Rauf, Andi Muhammad Ilham (Sangia Research Media and Publishing, 2024)
Labakkang District is the only coastal district in Pangkep Regency that has the potential for salt pond business activities. The people's salt farming business is a business that has been carried out by the people in this area for a long time, but there are several problems, namely the large amount of unused land, low quality of salt, low selling price and lack of market absorption, therefore a study is needed to see the sustainability status of the business. the. This research aims to determine the sustainability status of people's salt businesses in Labakkang District, Pangkep Regency. The analytical method used in this research is sustainability status analysis with